2008
DOI: 10.1007/s00774-008-0857-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cell-cell and cell-matrix interactions in bone destruction induced by metastatic MDA-MB-231 human breast cancer cells in nude mice

Abstract: To clarify the mechanisms of bone destruction associated with bone metastases, we studied an animal model in which inoculation of MDA-MB-231 human breast cancer cells into the left cardiac ventricle of female nude mice causes osteolytic lesions in bone using morphological techniques. On the bone surfaces facing the metastatic tumor cells, there existed many tartrate-resistant acid phosphatase (TRAP)-positive multinucleated osteoclasts. TRAP-positive mononuclear osteoclast precursor cells were also observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
14
0
1
Order By: Relevance
“…Also, TGF␤ increases production of parathyroid hormone-related peptide by the tumor cells to induce osteoclastic activity in the bone microenvironment. In fact, using the same mouse model of MDA-MB-231 breast cancer cell metastasis to bone used in this study, Nakamura et al (58) recently showed the presence of the tumor cells positive for parathyroid hormone-related peptide facing the bone surface where the multinucleated osteoclasts are lined (58). Also in the tumor nest, CD44 immunoreactivity was observed with colocalization of hyaluronan.…”
Section: Cd44supporting
confidence: 52%
“…Also, TGF␤ increases production of parathyroid hormone-related peptide by the tumor cells to induce osteoclastic activity in the bone microenvironment. In fact, using the same mouse model of MDA-MB-231 breast cancer cell metastasis to bone used in this study, Nakamura et al (58) recently showed the presence of the tumor cells positive for parathyroid hormone-related peptide facing the bone surface where the multinucleated osteoclasts are lined (58). Also in the tumor nest, CD44 immunoreactivity was observed with colocalization of hyaluronan.…”
Section: Cd44supporting
confidence: 52%
“…CD44, a transmembrane glycoprotein, is a major adhesion molecule for the extracellular matrix (ECM) that binds primarily to the extracellular glycosaminoglycan hyaluronan (HA). HA is a major non-protein glycosaminoglycan component of the ECM in human bone matrix, and the interaction of CD44 and HA facilitates tumor cell arrest and colonization in bone, leading to increased bone metastasis (24,30).…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining for CD44 and HA was conducted as described previously (21). Cell nuclei were stained with 4 0 ,6-diamidino-2-phenylindole (DAPI).…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%